Accelerating optimistic HLA-based simulations in virtual execution environments - Li, Zengxiang (2013)
High Level Architecture (HLA)-based simulations employing optimistic synchronization allows federates to process event and to advance simulation time freely at the risk of over-optimistic execution and execution rollbacks. In this paper, an adaptive resource provisioning system is proposed to accelerate optimistic HLA-based simulations in Virtual Execution Environment (VEE). A performance monitor is introduced using a middleware approach to measure the performance of individual federates transparently to the simulation application. Based on the performance measurements, a resource manager distributes the available computational resources to the federates, making them advance simulation time with comparable speeds. Our proposed approach is evaluated using a real-world simulation model with various workload inputs and different parameter settings. The experimental results show that, compared with distributing resources evenly among federates, our proposed approach can accelerate the simulation execution significantly using the same amount of computational resources.